Registration of Five Grain Sorghum Lines with Early‐Season Seedling Cold Tolerance. Issue 3 (1st September 2019) - Burke, John J.; Emendack, Yves; Hayes, Chad; Xin, Zhanguo; Burow, Gloria
Abstract : Five sorghum [ Sorghum bicolor (L.) Moench subsp. bicolor] germplasm lines, PSLS‐CTB06 (Reg. no. GP‐884, PI 687139), PSLS‐CTR07 (Reg. no. GP‐885, PI 687140), PSLS‐CTR08 (Reg. no. GP‐886, PI 687141), PSLS‐CTB09 (Reg. no. GP‐887, PI 687142), and PSLS‐CTB10 (Reg. no. GP‐888, PI 687143), were developed by the USDA‐ARS in Lubbock, TX. The primary purpose for the release of these lines is to provide an alternative germplasm choice with superior early‐season cold tolerance. PSLS‐CTB06 is derived from the plant introduction PI 452707, PSLS‐CTR07 is derived from the plant introduction PI 568351, PSLS‐CTR08 and PSLS‐CTB09 are derived from the plant introduction PI 452808, and PSLS‐CTB10 is derived from the plant introduction PI 452605. These lines derived from selected PI germplasm were evaluated for final germination percentages and vigor ratings in the field under cold conditions in 2015 and 2016. For public and private breeders, these new germplasm lines are an additional source for improving abiotic stress tolerance in diverse sorghum production environments.